HUBUNGAN ANTARA INTEGRITAS INFORMASI DENGAN JUDGMENT ATAS KINERJA DAN KEYAKINAN JUDGMENT DARI AUDITOR BADAN PEMERIKSA KEUANGAN RI - Noviana Dias Susanti; Faisal Faisal (Diponegoro Journal of Accounting, 2015)
Information integrity becomes one of the important aspects to be considered when making decisions in some areas of the accounting profession. Information integrity refers to the belief that a representative on the information presented to the user. Information integrity impairment in the financial statements, that is a summary of the various accounting transactions, are vulnerable place. Therefore, the accounting professional (including auditors) is expected to have the ability to identify the limitations of the information provided. Information integrity has several attributes. This study examines the effect of the four attributes of information integrity (completeness, currency, accuracy, and authorization) on performance judgment and judgment confidence of the auditor at the Audit Board of the Republic of Indonesia (BPK RI).Research conducted on the auditors who are conducting education and training at the BPK Training Center in Yogyakarta. The number of respondents in this study were 56 respondents. This study uses primary data in the form of a questionnaire. MANOVA analysis testing techniques used to prove the research hypothesis.The results show that there is a relationship between the information integrity with the performance judgment and judgment confidence. However, in this study, the auditor does not consider the four attributes of information integrity in assessing the performance and confidence ratings. The auditor considers elements of completeness, accuracy, and authorization information in its judgment, while the element currency is not present. There are many things that may cause the results of these tests, including factors experience of auditos, technical ability auditor, the auditor's knowledge, and so on.